Giant magnetoresistive properties of FexAu100-x alloys produced by mechanical alloying - Socolovsky, Leandro Martin (2001)
The FexAu100-x alloys were produced for the first time by mechanical alloying. Resistance of samples with iron concentrations of x = 15, 20, 25, and 30 at% were measured at 77 K under an applied field of 14 kOe. A maximum in magnetoresistive ratio (Δp/p) of 3.5% was obtained for Fe25Au75. Samples were annealed in order to enhance magnetoresistive properties. These samples exhibit larger ratios, primarily due to the elimination of defects. X-ray diffraction Mössbauer spectroscopy and magnetoresistance measurements were performed, in order to correlate bulk and hyperfine magnetic properties with crystalline structure. X-ray diffractograms show an FCC structure, with no evidence for a BCC one. © 2001 Elsevier Science B.V. All rights reserved.